Epoxidation modification of strictly alternating copolymer via living and controlled anionic alternating copolymerization of 1,3-pentadiene and styrene derivatives - Xiong, Qiaoqiao; Yang, Shuai; Peng, Chengjun; Xie, Fengli; Gu, Zhuowei; Fu, Yawen; Tan, Haoyun; Dai, QiQi; Yi, Wenjun; Li, Lijun; Liu, Kun (Journal of polymer research, 2023)
Styrene/1,3-diene copolymers are widely used in rubber tires, adhesives, waterproof materials, automotive parts and others. However, their oil resistance, compatibility with polar materials, and poor adhesion limit their applications. Polarization modification strategy can further expand the application field of such materials. In this paper, a series of strictly alternating copolymers were synthesized in cyclohexane via living and controlled anionic alternating copolymerization of styrene derivatives (including styrene (ST), p -methylstyrene (MST), p -tert-butylstyrene (TBS), and 1,1-diphenylethylene (DPE)) with 1,3-pentadiene (PD) using n -BuLi initiator. The above-mentioned alternating copolymers were epoxidized in cycloamyl methyl ether (CPME, green solvent) using m -Chloroperoxybenzoic acid ( m -CPBA) as the oxygen source. The 1 H NMR and FTIR results showed that the degree of epoxidation ( DE ) of the alternating copolymers was controllable and the cross-linking gels can be avoided (determined by solubility experiment), and the DE of nearly 100% could be achieved by optimizing processes. As for these PD-based alternating copolymers, the type of substituents on rigid benzene rings has a certain impact on the epoxidation rate as well as the DE . DSC results showed that not only the high steric hindrance groups in polymer side chains but also the epoxidation strategy can greatly improve the heat resistance of the product.